EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PERENCANAAN MASA DEPAN KARIR ANAK ASUH PANTI ASUHAN AISYIYAH PUTRA BUKITTINGGI - Siti Aisyah; Syawaluddin Syawaluddin; Cilung Ardizo (CV. ADIBA AISHA AMIRA, 2023)
Career planning is a series of jobs, titles and positions that are carried out throughout life and seem to be very beneficial for life. Career also means the status of a job level or position as a source of income, whether in the form of a main livelihood or a side income. The aim of this research is to test the effectiveness of group guidance services to improve future career planning for children fostered at the Aisyiyah Putra Bukittinggi orphanage. The researcher used a pre-experimental research method approach, one group pre-test post-test. The population in the study were foster children at the Aisyiyah Putra Bukittinggi orphanage who did not yet have an understanding of planning for the future. The data analysis technique uses the Wilcoxon Rank Test. The instrument used is the questionnaire. Wilcoxom Rank Test analysis shows a value of 0.028 which is lower than 0.05. So it is concluded that the application of group guidance services to the future career planning of the foster children at the Aisyiyah Putra Bukittinggi orphanage is increasing and being provided effectively.